2016 IEEE International Conference on Advanced Intelligent Mechatronics (AIM) 2016
DOI: 10.1109/aim.2016.7576855
|View full text |Cite
|
Sign up to set email alerts
|

TIREBOT: A novel tire workshop assistant robot

Abstract: In this paper a novel tire workshop assistant robot is presented. The robot can load heavy wheels and transport them in any place of the workshop, lifting the operator from the effort of doing it manually. The operator can interact with the robot through gestures, which are captured by a RGB-D camera and translated into commands, or teleoperate it through a control station equipped with a haptic interface, which can also return a force feedback. The robot can also operate autonomously with a mission manager th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Therefore, to eliminate employee risks and fatigue, it is necessary to develop robots that would complement human labor in heavy or repetitive work. Levratti, A. et al introduce a modern tire workshop assistant robot which can bear heavy wheels and transfer them to any spot in the workshop, and can be interacted with either via gestures or tele-operatively through a haptic interface [15]. Further, Peternel, L. et al propose a method to enable robots to adapt their behavior to human fatigue in human-robot co-manipulation tasks.…”
Section: Industrial Application Of Collaborative Robots: Assemblymentioning
confidence: 99%
“…Therefore, to eliminate employee risks and fatigue, it is necessary to develop robots that would complement human labor in heavy or repetitive work. Levratti, A. et al introduce a modern tire workshop assistant robot which can bear heavy wheels and transfer them to any spot in the workshop, and can be interacted with either via gestures or tele-operatively through a haptic interface [15]. Further, Peternel, L. et al propose a method to enable robots to adapt their behavior to human fatigue in human-robot co-manipulation tasks.…”
Section: Industrial Application Of Collaborative Robots: Assemblymentioning
confidence: 99%
“…The odometry used in the omnidirectional mobile APR-02 is based on the kinematic analysis described in the previous Section 3. 4. This kinematic model converts the information of the angular rotational speed of the wheels of the omnidirectional mobile robot (ω a , ω b , ω c ) into an estimation of the motion of the mobile robot v x , v y , ω relative to the robot reference frame.…”
Section: Static Rotation Without Translationmentioning
confidence: 99%
“…The popularity of vehicles using an omnidirectional motion system in the field of robotics is on the rise [1][2][3]. An omnidirectional motion is one of the principal requirements for mobile robots designed to operate in complex and unstructured environments in order to develop services such as workshop assistance [4], domestic [5] or home assistance [6] and health-care assistance [7]. The main benefit of an omnidirectional motion system is that it provides three degrees of freedom (DOFs) in a ground plane, allowing displacements in any direction while changing its orientation.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of industrial robotics, many manufacturing applications are also reported in literature, ranging from load-ing and transporting heavy wheels [Levratti et al, 2016], collaborative assembly of a homokinetic mechanical joint [Cherubini et al, 2013, Cherubini et al, 2016 and cellular phones [Tan et al, 2009]. Another application within this field was presented in [Erden and Billard, 2014].…”
Section: Benchmarking and Relevant Use Casesmentioning
confidence: 99%